Effect of microwave power on morphology of AgO thin film grown using microwave plasma CVD. (2018) - Ansari, Akhalakur Rahman; Imran, Mohd; Yahia, I.S.; Abdel-Wahab, Mohamed Shaaban; Alshahrie, Ahmed; Khan, Afzal Husain; Sharma, Chandan
In this study, pure silver (Ag) thin film of 8 nm was deposited onto glass substrate by using radio frequency (RF) sputtering technique and was then exposed to microwave assisted oxygen plasma generated by microwave plasma CVD. The oxidation of Ag into AgO thin film was studied using varying microwave power. The influence of microwave power on morphology and size of oxide film was investigated. The crystal structure, crystal size, chemical composition, morphologies and optical properties of oxidised silver thin film (AgO) was characterised by using x-ray powder diffraction (XRD), field emission scanning electron microscopy (FESEM), Raman spectroscopy and UV-vis spectroscopy. Morphological characterisation of these films reveals a systematic change from metallic silver (Ag) to silver oxide (AgO). The size of AgO thin film was calculated using Scherrer equation and was observed to be 11 nm, 12 nm and 13.5 nm at 400 W, 800 W and 1200 W respectively. A considerable change in UV-vis spectra was observed with increase in annealing temperature.